Chemopreventive properties of South African herbal teas, rooibos (Aspalathus linearis) and honeybush (Cyclopia spp) : mechanisms against skin carcinogenesis - Magcwebeba, Tandeka Unathi (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.